Evaluating U-Turn Capacity with Modified Geometry Designs and Various Conflicting Traffic Flows: A Traffic Microsimulation Approach - Fauzan Rizki Muharam; Taufiq S. Nugroho; Widyarini Weningtyas (Institute of Research and Community Outreach - Petra Christian University, 2025)
Factors such as U-turn geometric and conflicting traffic volume often play a key role on U-turn capacity and safety. Evaluating U-turn capacity under modified geometric designs and various conflicting traffic flow conditions thus is essential to improving traffic flow and safety. This paper analysis U-turn capacity under various conflicting traffic conditions and propose the U-turn geometry modifications to improve capacity. A microsimulation model using PTV VISSIM is developed, and the results is compared with conventional analytical method to highlight the advantages of using traffic microsimulation approach in such analyses. The results show that U-turn capacity is significantly affected by conflicting traffic flow that in turn affecting headway time, and service time for various vehicle type. Among the geometric modifications tested, channelization designs showed significant increase in capacity whilst roundabout and indirect right-side design give mixed results depending on the composition of vehicles performing U-turns.